2007
DOI: 10.1002/mame.200700147
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Morphological Studies of Poly(propylene)‐Filled Eggshell Composites

Abstract: Poly(propylene) (PP) composites were prepared by using eggshell (ES) as filler and their mechanical properties were compared with those using talc (TA) and calcium carbonate (CC) of different grain sizes (X50). A decrease in impact strength and deformation at break with increase in filler content was observed. The PP composite with ES (X50 = 8.4 µm) was stiffer than those with CC (X50 = 0.7 µm). The hybrid composite PP‐ES‐TA showed a similar stiffness as the PP‐TA composites due to the similar morphology of TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…The improvement of the adhesion is a key factor, poor interfacial region weakens the composite. Toro [6] pointed that when a crack is generated due to an impact it is propagated towards poor interfacial regions, so the composite is broken easily.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The improvement of the adhesion is a key factor, poor interfacial region weakens the composite. Toro [6] pointed that when a crack is generated due to an impact it is propagated towards poor interfacial regions, so the composite is broken easily.…”
Section: Figurementioning
confidence: 99%
“…So, the effect of each filler particle over the flexural modulus is superposed, which lead to the flexural modulus increasing evidently. [6] where the ES has been added into a polypropylene matrix. It is observed that the tensile strength for the composites decreases with increasing filler content.…”
Section: Second Stage Study Of the Filler Loading Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…The use of inorganic fillers in polymer industry is known to be widely economical due to their low cost, while introducing efficient advantages of both polymer materials and inorganic compounds (Toro et al, 2007;Zhao et al, 2012). Furthermore, incorporating finely distributed solid particles into semicrystalline polymers such as polyolefins and polyamides can provoke nucleation which is essential in industrial applications to control the polymer structure via crystallization and also to shorten the cycle time of crystallization (Göschel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These goals can be partially fulfilled by using natural and waste fillers in polymeric matrice. Past studies have underlined the use of mineral fillers from bio-based and renewable resources including rice husk ash [6,7], eggshell (ES) powder [8,9], and cuttlebone [10,11] to tackle the cost problem of products, at the same time as far as possible promote their properties (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%